Origin of the unusually strong and selective binding of vanadium by polyamidoximes in seawater - Alexander S. Ivanov (Nature Portfolio, 2017)
Amidoxime-functionalized polymeric adsorbents are the most promising materials for harvesting uranium from seawater. Here the authors investigate the preferential extraction of vanadium over uranium by polyamidoximes by exploring the unusually strong and selective binding of vanadium.